2012
DOI: 10.1039/c2cp23840c
|View full text |Cite
|
Sign up to set email alerts
|

LIAD-fs scheme for studies of ultrafast laser interactions with gas phase biomolecules

Abstract: Laser induced acoustic desorption (LIAD) has been used for the first time to study the parent ion production and fragmentation mechanisms of a biological molecule in an intense femtosecond (fs) laser field. The photoacoustic shock wave generated in the analyte substrate (thin Ta foil) has been simulated using the hydrodynamic HYADES code, and the full LIAD process has been experimentally characterised as a function of the desorption UV-laser pulse parameters. Observed neutral plumes of densities >10(9) cm(-3) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 47 publications
(67 reference statements)
2
44
0
Order By: Relevance
“…Phenylalanine was deposited on a 10-µm-thick stainless steel foil, mounted onto the repeller electrode of a time of flight (TOF) mass spectrometer [31]. To evaporate the sample, the reverse side of the foil was irradiated with a CW diode laser operating at a wavelength of 960 nm, with a spot diameter of 6 mm and power in the range 0.3 -0.4 W. The distance from the foil to the focal point of the ionizing laser pulses was approximately 3 mm.…”
Section: Methodsmentioning
confidence: 99%
“…Phenylalanine was deposited on a 10-µm-thick stainless steel foil, mounted onto the repeller electrode of a time of flight (TOF) mass spectrometer [31]. To evaporate the sample, the reverse side of the foil was irradiated with a CW diode laser operating at a wavelength of 960 nm, with a spot diameter of 6 mm and power in the range 0.3 -0.4 W. The distance from the foil to the focal point of the ionizing laser pulses was approximately 3 mm.…”
Section: Methodsmentioning
confidence: 99%
“…We have overcome these issues, however, through the use of a "soft" laser desorption method based on back-irradiation of thin foil targets coated with the molecular samples of interest [42] [43]. In the present study we have sought to remedy this situation by obtaining the first reported gas-phase measurements of ππ* excited state decay in all of the DNA nucleosides following UV excitation.…”
Section: Introductionmentioning
confidence: 99%
“…These amino acids were chosen as model molecules for charge transfer because they each have a radical cation with two charge-acceptor sites at approximately the same binding energy located on the phenyl and amine groups, separated by two singly bonded carbon. Clean plumes of isolated, neutral molecules were produced by a laser induced acoustic desorption (LIAD) technique [46]: a UV desorption laser was focused on the uncoated side of a thin (thickness of 10 µm) tantalum foil, the acoustic wave produced by the UV laser volatilized the sample on the other side of the foil, thus creating a molecular plume in the source region of a Time of Flight (TOF) mass spectrometer. Compared to direct laser desorption methods, LIAD leads to less energy coupling into the molecules, thus giving the possibility to produce fragile neutral molecules with lower internal temperature [46].…”
Section: Electron Dynamics In Biomoleculesmentioning
confidence: 99%